Implementation of Green Accounting at PT Cirebon Electric Power - Safira, Adinda; Oktaviani, Devira; Ayu, Putri Puspita (Rescollacom (Research Collaborations Community), 2024)
The aim of this research was written by researchers to determine and analyze the implementation of Green Accounting at PT Cirebon Electric Power on the company's environmental performance and costs. This research was conducted because researchers wanted to analyze Green Accounting or environmental accounting at PT Cirebon Electric Power , whether the implementation of Green accounting was going well or not. Pollution that occurs due to the production process and waste produced by companies has caused the Indonesian government to plan to implement the Cirebon Steam Power Plant (PLTU) operational shutdown program sooner than initially planned. The method used in this research is a qualitative method with data collection techniques using interviews. The resource persons in this research were company employees from the environment division. The research results show that the implementation of Green Accounting at PT Cirebon Electric Power regarding environmental performance and costs has been implemented well. In implementing Green Accounting at PT Cirebon Electric Power, the performance rating obtained by the company is a green rating, which means that a company's environmental management performance assessment has achieved good environmental management performance. PT Cirebon Electric Power in implementing Green Accounting has 3 environmental costs , namely: prevention costs, planning costs and unexpected costs. These environmental costs do not have a direct impact on company profits, each year environmental costs are budgeted by each share holder for operational implementation and prevention of environmental impacts.